Turning the tumor microenvironment into a self vaccine site - Nelson, Delia (2012)
We aimed to determine if the tumor microenvironment could be turned into a "self"-vaccine site. We show that provoking a local inflammatory response modulates endothelia to permit the infiltration of innate and adaptive effector cells which collaborateto eradicate the inflamed tumor and other tumor deposits, and provide long-term protection. © 2012 Landes Bioscience.